Assessing the extent to which current clinical research is consistent with patient priorities: a scoping review using a case study in patients on or nearing dialysis. Issue 1 (December 2015) - Jun, Min; Manns, Braden; Laupacis, Andreas; Manns, Liam; Rehal, Bhavdeep; Crowe, Sally; Hemmelgarn, Brenda
Abstract Purpose of review There is growing acknowledgement that engaging patients to identify their research priorities is important. Using a case study of patients on or nearing dialysis, we sought to assess the extent to which recently completed and ongoing clinical research was consistent with priorities identified by patients, caregivers, and clinicians. Sources of information Over a 4-year sampling frame (January 2010 to December 2013), we systematically searched the medical literature (top 5 nephrology and top 10 general medicine journals accessed through MEDLINE via Ovid), international randomized controlled trial (RCT) registries, and national government and kidney research funding organizations (Canada, U.S., Australia, and U.K.) for published clinical studies, registered RCTs, and funded clinical studies, respectively. Published clinical studies, registered RCTs, and funded clinical studies were categorized as to whether or not they were consistent with the top 10 research priorities identified by patients, their caregivers, and clinicians in a recent comprehensive research priority setting exercise. Findings The search yielded 4293 published articles, 688 RCTs, and 70 funded studies, of which 1116 articles, 315 RCTs, and 70 funded studies were eligible for inclusion. Overall 194 published studies (17.4 %), 71 RCTs (22.5 %), and 15 funded studies (21.4 %) included topics consistent with the top 10 research priorities identified by patients. Four of the top 10 research priorities, including strategies to improve the management of itching, increase access to kidney transplantation, assess the psychosocial impact of kidney failure, and determine the effects of dietary restriction received virtually no attention. Limitations The top 10 priorities we used to categorize included studies were identified by Canadian patients, caregivers, and clinicians. The top research priorities may vary across different countries. The proportion of published studies that are consistent with the top 10 priorities could be different in nephrology journals with lower impact factors. Studies related to kidney transplantation and the psychosocial impact of kidney failure may have been published in journals not included in our search strategy. Implications The majority of recently completed or ongoing clinical studies in patients on or nearing dialysis do not address the top research priorities of patients, raising concerns that current clinical research may not be meeting the needs of the ultimate consumer, in this case, patients on or nearing dialysis. Greater involvement of patients in research is required to bridge the gap between research and patients' needs. Abrégé Objectifs de l'étude Il apparait de plus en plus important de consulter les patients afin de mieux répondre à leurs attentes vis-à-vis de la recherche clinique. Lors d'une étude de cas faite sur des patients en dialyse ou sur le point d'en entreprendre une, nous avons voulu savoir à quel point les études cliniques en cours ou complétées récemment étaient en accord avec les priorités de recherche établies par les patients, le personnel soignant et le personnel clinique. Sources Pour ce faire, nous avons dressé un portrait de la situation sur une période de quatre ans (de janvier 2010 à décembre 2013). Nous avons passé en revue de façon systématique la littérature médicale (les cinq meilleures revues scientifiques en néphrologie et les dix journaux de médecine générale les plus cités accessibles sur MEDLINE via Orbid) ainsi que les registres internationaux d'essais cliniques. Nous avons répertorié les études cliniques publiées, les essais cliniques déposés et les études cliniques financées au privé parmi les publications gouvernementales à l'international (Canada, États-Unis, Australie et Royaume-Uni) et les rapports des organismes finançant la recherche sur les maladies du rein. Nous voulions évaluer la cohérence entre les objectifs et résultats de ces recherches et les dix principales attentes des patients, du personnel soignant et du personnel clinique face à celles-ci. Constatations La recherche a mené à une liste de 4293 articles publiés, 688 essais cliniques et 70 études cliniques financées, de laquelle 1116 articles, 315 essais cliniques et 70 études cliniques financées étaient admissibles à satisfaire nos critères de recherche. Finalement, seulement 194 articles publiés (17.4 %), 71 essais cliniques (22.5 %) et 15 études financées (21.4 %) mentionnaient l'une ou l'autre des dix priorités de recherche établies par les patients, le personnel soignant ou le personnel clinique. Quatre de leurs préoccupations principales, soit la façon d'améliorer le traitement des démangeaisons, l'accès accru aux transplantations rénales, l'évaluation de l'impact de l'insuffisance rénale au point de vue psychosocial chez le patient atteint ainsi que la détermination des risques potentiels posés par les restrictions alimentaires sévères, n'ont reçu que très peu d'attention parmi les sources passées en revue. Limites de l'étude La liste des dix priorités de recherche utilisée pour classer l'information recueillie parmi les sources citées avait été établie par des patients, du personnel soignant et du personnel clinique canadien seulement. Ces priorités pourraient varier d'un pays à l'autre. Aussi, le passage en revue des journaux de néphrologie de moindre importance aurait possiblement mené à des résultats différents. Il est tout à fait possible que des études sur l'impact au point de vue psychosocial de l'insuffisance rénale aient été publiées dans des journaux n'ayant pas fait partie de notre stratégie de recherche. Conséquences Il ressort de cela que la majorité des études cliniques en cours ou complétées dans les dernières années ayant été faites sur des patients en dialyse ou sur le point d'en entreprendre une n'abordait pas les principales attentes des patients. Ce fait est préoccupant puisqu'il implique que la recherche actuelle ne répond pas adéquatement aux besoins des gens à qui elle s'adresse ultimement. Par conséquent, l'implication plus directe des patients dans la recherche est requise pour établir des ponts et réduire l'écart entre celle-ci et les besoins réels des usagers.